The highly divergent Jekyll genes, required for sexual reproduction, are lineage specific for the related grass tribes Triticeae and Bromeae. (25th May 2019) - Radchuk, Volodymyr; Sharma, Rajiv; Potokina, Elena; Radchuk, Ruslana; Weier, Diana; Munz, Eberhard; Schreiber, Miriam; Mascher, Martin; Stein, Nils; Wicker, Thomas; Kilian, Benjamin; Borisjuk, Ljudmilla
Summary: Phylogenetically related groups of species contain lineage‐specific genes that exhibit no sequence similarity to any genes outside the lineage. We describe here that the Jekyll gene, required for sexual reproduction, exists in two much diverged allelic variants, Jek1 and Jek3 . Despite low similarity, the Jek1 and Jek3 proteins share identical signal peptides, conserved cysteine positions and direct repeats. The Jek1/Jek3 sequences are located at the same chromosomal locus and inherited in a monogenic Mendelian fashion. Jek3 has a similar expression as Jek1 and complements the Jek1 function in Jek1 ‐deficient plants. Jek1 and Jek3 allelic variants were almost equally distributed in a collection of 485 wild and domesticated barley accessions. All domesticated barleys harboring the Jek1 allele belong to single haplotype J1‐H1 indicating a genetic bottleneck during domestication. Domesticated barleys harboring the Jek3 allele consisted of three haplotypes. Jekyll ‐like sequences were found only in species of the closely related tribes Bromeae and Triticeae but not in other Poaceae. Non‐invasive magnetic resonance imaging revealed intrinsic grain structure in Triticeae and Bromeae, associated with the Jekyll function. The emergence of Jekyll suggests its role in the separation of the Bromeae and Triticeae lineages within the Poaceae and identifies the Jekyll genes as lineage‐specific. Significance Statement: The Jekyll gene, required for sexual reproduction, exists in two much diverged allelic variants that share little similarity in sequences but have common functions of the encoded proteins. Jekyll was found only in species of the related tribes Bromeae and Triticeae suggesting its role in tribe separation within the Poaceae. The emergence of Jekyll coincided with innovations in grain structure of the Bromeae and Triticeae lineages and identifies the Jekyll genes as lineage specific.